2000
DOI: 10.2151/jmsj1965.78.2_175
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of GPS Precipitable Water at Lhasa in Premonsoon and Monsoon Periods

Abstract: In this study, precipitable water is estimated from GPS data with high time resolution at Lhasa. Mean precipitable water in the premonsoon and the monsoon periods are about 10mm and 25mm, respectively, while precipitable water increases in short term at around the onset. Prominent diurnal variation of precipitable water can be observed in both periods. The minima of the diurnal variation appear around 1800 LST and 1500 LST in the premonsoon and the monsoon periods, respectively. These characteristics indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Diurnal variations in PW have been observed by GPS at Lhasa during the pre-monsoon and monsoon (Takagi et al 2000). During the summer monsoon, PW decreases from morning until 15 LST and then increases until 21 LST.…”
Section: Characteristics Of Diurnal Variations In Convection and Precmentioning
confidence: 96%
“…Diurnal variations in PW have been observed by GPS at Lhasa during the pre-monsoon and monsoon (Takagi et al 2000). During the summer monsoon, PW decreases from morning until 15 LST and then increases until 21 LST.…”
Section: Characteristics Of Diurnal Variations In Convection and Precmentioning
confidence: 96%
“…Kuwagata et al (2001) discussed the horizontal transport of moisture by thermally induced local circulation in the major topography of the Tibetan Plateau after showing that most observation stations are located in valley regions. By analyzing GPS precipitable water, Takagi et al (2000) demonstrated that precipitable water decreases in the daytime at Lhasa, which is located at the bottom of a valley (shown in Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported decreases in PWV in the daytime over inland, mountainous, and coastal areas and have concluded that local circulations are important to this process (Takagi et al 2000;Bastin et al 2007). Under such conditions, convective activity might be closely related to a local circulation.…”
Section: Discussionmentioning
confidence: 98%
“…Recent progress in collecting in situ observation variables has made it possible to measure precipitable water vapor (PWV) at a high time resolution (e.g., Takagi et al 2000). Passive microwave radiometry, which was adopted in this study, is an efficient method to retrieve continuous profiles of atmospheric humidity and temperature (Lohnert et al 2007).…”
Section: Introductionmentioning
confidence: 99%